Matra Basti- Mode of Action-A Conceptual Study - Patidar, Anil; Mangal, Gopesh; Sharma, Siddharth (International Research Journal of Ayurveda & Yoga, 2022)
The five-bio cleansing/detoxifying procedures (Panchakarma procedures/ Samshodhan Chikitsa) advocated in Ayurveda are Vaman (Therapeutic emesis), Virechan (Therapeutic Purgation), Basti (Medicated Enema), Nasya (Infiltration of medications through nostrils), and Raktamokshana (Bloodletting by different methods). The therapeutic oil or herbal decoction is administered through the anal route in Basti Karma. Ayurveda considers Basti Chikitsa to be one of the most important Panchakarma treatments. It contains both therapeutic and preventative as well as promotional properties. This Basti therapy also helps to relieve tension in the body and mind, hence improving one’s quality of life. The rectum is used to administer herbal decoctions and therapeutic oils to the colon. It is not a localised or symptomatic treatment, despite the fact that it directly affects the colon. Vatahara, Shulahara, Shothahara, Srotoshodhaka, Yogavahi, Agnideepaka, and Rasayana are some of the roles that Basti Dravyas can play. Matra Basti is an oil/unctuous substance-free therapy. Abhyanga (therapeutic oil massage) and Swedana are performed before to it (sudation). Human is the king of the castle (body) so he has to make the decisions how to convert it into more beautiful and healthy state along with its prevention from the rust of impurities. The current article summarises the ayurvedic perspective on Matra basti and its mode of action.